Morphology of the Dentate Gyrus in a Large Cohort of Sudden Infant Deaths—Interrelation Between Features but Not Diagnosis. Issue 1 (3rd December 2021) - Machaalani, Rita; Vivekanandarajah, Arunnjah; Despotovski, Vanessa; Rodriguez, Michael; Waters, Karen A
Abstract: Morphological differences in the dentate gyrus (DG) have been reported in sudden unexpected deaths in infancy (SUDI), with the feature of focal granule cell (GC) bilamination (FGCB) reported as increased in unexplained SUDI, including sudden infant death syndrome (SIDS), compared with explained SUDI (eSUDI). However, it remains to be determined how these morphologies relate to each other and their extent along the anteroposterior length. This retrospective study evaluated the prevalence of FGCB, single or clustered ectopic GCs, granule cell dispersion (GCD), heterotopia, hyperconvolution, gaps, thinning, blood vessel dissection (BVD), and cuffing (BV cuffing), in an Australian SUDI cohort, and compared the prevalence of these features in eSUDI and unexplained SUDI. We analyzed 850 formalin-fixed paraffin-embedded serial and subserial sections of the hippocampus at the level of the lateral geniculate nucleus from 90 infants, and identified GCD in 97% of infants, single ectopic cells, hyperconvolution, thinning, and BVD in 60%-80%, heterotopia in 36%, gaps, clusters of ectopic cells and BV cuffing in 9%–15%, and FGCB in 18%. These features are clustered within 3–5 serial sections. The presence of FGCB correlated with single ectopic GCs and hyperconvolution. There were no differences in the prevalence of these features between unexplained SUDI (n = 74) and eSUDI (n = 16). Our findings highlight that DG morphological features are highly localized, extending 14–35 µm at their focal location(s) along the anteroposterior length. Consequently, multiple sections along the longitudinal extent are required to identify them. No feature differentiated SUDI from eSUDI in our cohort, thus we cannot conclude that any of these features are abnormal and it remains to be determined their functional significance.